Screening and confirmation methods of the major urinary metabolite of finasteride-carboxy-finasteride by liquid chromatography-mass spectrometry and liquid chromatography-tandem mass spectrometry - Jianli Zhang (Elsevier, 2012)
Screening and confirmation methods of the major urinary metabolite of finasteride-carboxy-finasteride for doping control purpose were developed. Liquid-liquid extraction was adopted for the sample preparation. Analytes were detected by positive electrospray ionization in single quadrupole and triple quadrupole mass spectrometer. In the screening method, selected ion monitoring (SIM) mode was used to monitor m/z 403 for carboxy-finasteride. In the confirmation method, product ion mode was used to monitor the precursor ion m/z 403. The limit of detection was below 2 ng/mL for the screening method. Good linearity was obtained in the range 10.0-500.0 ng/mL. The intra-run and inter-run precision calculated from quality control (QC) samples was less than 5.3%. The accuracy as determined from QC samples was within ±6.6%. The screening method was applied for the analysis of excretion samples, allowing the detection of carboxy-finasteride for up to 49 h in urine specimen collected after an oral administration of 5 mg of finasteride.